2019
DOI: 10.1007/s11914-019-00509-x
|View full text |Cite
|
Sign up to set email alerts
|

The Osteocyte as a Novel Key Player in Understanding Periodontitis Through its Expression of RANKL and Sclerostin: a Review

Abstract: Purpose of Review Periodontitis is the inflammation-associated bone loss disease of the alveolar bone that surrounds teeth. Classically, the emphasis on the etiology of periodontitis has been on the products of periodontal pathogens that lead to an inflammatory response of the soft tissues of the periodontium, eventually leading to activation of osteoclasts that degrade the alveolar bone. Until recently, the response of osteocytes that populate the alveolar bone, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
0
16
0
2
Order By: Relevance
“…The osteocyte population is a crucial regulator of both sclerostin and RANKL local expression during active periodontal disease (210). The sclerostin and RANKL are negative bone mass regulators by inhibiting Wnt signaling and by inducing osteoclastogenesis, respectively (210)(211)(212).…”
Section: Bone Conditions With Potential Muscle Implications In the Mamentioning
confidence: 99%
“…The osteocyte population is a crucial regulator of both sclerostin and RANKL local expression during active periodontal disease (210). The sclerostin and RANKL are negative bone mass regulators by inhibiting Wnt signaling and by inducing osteoclastogenesis, respectively (210)(211)(212).…”
Section: Bone Conditions With Potential Muscle Implications In the Mamentioning
confidence: 99%
“…We inhibited osteoclastogenesis by DHA which reduced the expression of the osteoclast-derived factor LIF, thereby increasing the expression of sclerostin that inhibits abnormal bone formation and remodeling of the subchondral bone. Sclerostin is an important factor in bone remodeling, and is affected by numerous factors ( 51 , 52 ). Previous studies have found that mechanical stimulation inhibit the expression of sclerostin ( 16 - 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sclerostin appears to be involved in the etiopathogenesis of PD, as knock out mice had a slightly ameliorated PD phenotype (119) and antibodies against sclerostin inhibited the progression of PD (116). Even more interesting, sclerostin antibodies were able to ameliorate inflammation and to partially revert PD related bone damage (118). In conclusion, osteocytes are a source of important mediators of bone in periodontitis.…”
Section: Resident Periodontal Cellsmentioning
confidence: 92%
“…Sclerostin antagonizes canonical Wnt-signaling directly by binding to the LRP5/6 receptor, while DKK1 exerts its action by binding to the Wnt coreceptor (116,117). Osteocytes express and secrete sclerostin and DKK1 (118).…”
Section: Resident Periodontal Cellsmentioning
confidence: 99%